Progress of melatonin in the treatment of intervertebral disc degeneration - Yin, Jianlin; Wan, Lei; Zhang, Kuaixiang; Yang, Jiangjia; Liu, Man; Zhao, Mingyu; Li, Jitian (Frontiers in Physiology, 2025)
The most common degenerative condition affecting the musculoskeletal system, and the leading cause of persistent low back pain, is intervertebral disc degeneration (IDD). IDD is increasingly common with age and has a variety of etiologic factors including inflammation, oxidative stress, extracellular matrix (ECM) degradation, and apoptosis that interact with each other to cause IDD. Because it is difficult to determine the exact pathogenesis of IDD, there is a lack of effective therapeutic agents. Melatonin has been intensively studied for its strong anti-inflammatory, antioxidant, and anti-apoptotic properties. Melatonin is a pleiotropic indole-stimulating hormone produced by the pineal gland, which can be used to treat a wide range of degenerative diseases. Therefore, melatonin supplementation may be a viable treatment for IDD. This article reviews the current mechanisms of IDD and the multiple roles regarding melatonin’s anti-inflammatory, antioxidant, anti-apoptotic, and mitigating ECM degradation in IDD, incorporating new current research perspectives, as well as recent studies on drug delivery systems.